Pengaruh Kompensasi, Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan ( Studi Pada Karyawan PT.Tam Cargo Cabang Surabaya ) - Zein Ilham Pratama; Adrianto Trimarjono (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2022)
In research conducted on employees of PT. TAM Cargo Surabaya branch aims to determine whether compensation, work discipline, and work motivation have a significant influence on the performance of the company's employees. In this study, the data used came from the results of questionnaires, observations, and literature studies related to the research. The technical analysis used is multiple linear regression using the T hypothesis test. The number of samples used is 40 respondents with non-probability sampling technique. The results showed that the performance of the employees of PT. TAM Cargo Surabaya branch is affected by compensation and work discipline. While the work motivation variable does not show a significant effect